The role of organizational citizenship behavior and patriotism in sustaining public health employees’ performance - Rizaie, Mohammad Eqbal; Horsey, Emmanuel Mensah; Ge, Zhangzhi; Ahmad, Nisar (Frontiers in Psychology, 2023)
Employee performance during health crises is currently one of the most alarming global concerns. Owing to its significance, scholars assessed factors that improve such performance. However, such improvements in performance require public health employees’ discretionary behavior. We investigate the impact of organizational citizenship behavior and patriotism on employee performance, shifting the focus of the healthcare industry’s employee performance conversation to how it can be sustained. We used cross-section data from 541 Chinese public health employees who made up the final sample in this study, which has been shown to be appropriate for investigations utilizing a quantitative method. The results of our empirical analysis demonstrate that organizational citizenship behavior positively contributes to sustaining employee performance. We found the same to be true about the positive mediating effect of patriotism on the aforementioned relationship. The findings offer insights into how a country’s performance at both local and international levels propels and sustains the job performance of its citizenry. Thus, governments should be more efficient and ensure they maintain a robust institutional environment. This study provides theoretical and empirical evidence based on a research survey of the roles of organizational citizenship behavior and patriotism that sustain employee performance in China’s public health sector, in particular during health crises.